Konstruksi Masyarakat pada Tradisi Nyajen Sebagai Usaha Keberhasilan Cakades Jelang Pilkades - Nina Karerina; Aniq Ifadah; Sejati Ayuning Arisholina; Ayu Wulaningsih; Luki Ricard; Agus Machfud Fauzi (Jurnal Penelitian Agama, 2021)
Local beliefs and cultural values are still attached to the Javanese community, especially in the countryside. Karangpuri Village still preserves the tradition of its general, especially in political terms. Next April there will be a village head election. cakades carries on the tradition of iajen for the smooth running of the pilkades. This study uses a qualitative method with a descriptive approach with the foundation of Peter L. Berger's sosial construction theory. This research was conducted in Karangpuri Village, Sidoarjo. The goal is to find out the Karangpuri village community construction against the tradition of the generalthe results of this study are that the community sees this as normal and should be done by everyone who has a desire for fluency, pangestu to ancestors, and as a form of preserving local culture and beliefs inherited from previous ancestors.